Relationship Between Age and Rotator Cuff Retear: A Study of 1, 600 Consecutive Rotator Cuff Repairs. (19th July 2017) - Diebold, Georgia; Lam, Patrick; Walton, Judie; Murrell, George A.C.
Abstract : Background: The prevalence of rotator cuff tears increases with age, and many patients undergo surgical repair. Retears are not uncommon, with rates ranging between 9% and 36% in recent studies, and are a major concern. The aim of this study was to investigate the relationship between patient age and the chance of healing following rotator cuff repair. Methods: This was a retrospective cohort study of patients who had undergone arthroscopic rotator cuff repair performed by a single surgeon. All patients had an ultrasound performed by a musculoskeletal sonographer 6 months after rotator cuff repair to assess the repair integrity. Results: The cohort of 1, 600 patients was normally distributed in terms of age, with a mean age (and standard error of the mean) of 59 ± 0.3 years and a range of 15 to 91 years. The 212 patients (13%) who had a retear at 6 months were also normally distributed in terms of age, with a mean age of 65 ± 0.8 years and a range of 15 to 88 years. The retear rate in patients <50 years old was 5%. This increased to 10% in patients aged 50 to 59 years, 15% in those aged 60 to 69 years, 25% in those aged 70 to 79 years, and 34% in those aged ≥80 years. Multiple logistic regression analysis showed that patient age was an independent factor strongly associated with retears. Conclusions: The rate of rotator cuff retears is low in patients <50 years of age. The relationship between age and rotator cuff retears is linear in patients 50 to 69 years of age, with an increase of 5% between decades, and increases substantially in patients ≥70 years old. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.